Maternal caregiving capabilities are associated with child linear growth in rural Zimbabwe. Issue 2 (21st December 2020) - Tome, Joice; Mbuya, Mduduzi N. N.; Makasi, Rachel R.; Ntozini, Robert; Prendergast, Andrew J.; Dickin, Katherine L.; Pelto, Gretel H.; Constas, Mark A.; Moulton, Lawrence H.; Stoltzfus, Rebecca J.; Humphrey, Jean H.; Matare, Cynthia R.; et al.
Abstract: Between birth and 2 years, children's well‐being depends on the quality of care they receive from caregivers, primarily their mothers. We developed a quantitative survey instrument to assess seven psychosocial characteristics of women that determine their caregiving ability ('maternal capabilities': physical health, mental health, decision‐making autonomy, social support, mothering self‐efficacy, workload and time stress, and gender norm attitudes). We measured maternal capabilities in 4, 025 mothers and growth in their 4, 073 children participating in the Sanitation Hygiene Infant Nutrition Efficacy (SHINE) trial in rural Zimbabwe. We used generalized estimating equation models with exchangeable correlation structure to test the association between each maternal capability during pregnancy, and infant length‐for‐age Z (LAZ) at 18 months, accounting only for within‐cluster correlation and intervention arms in unadjusted analyses and for potential confounders in adjusted analyses to examine the association between each capability, assessed during pregnancy, with child LAZ at 18 months of age. In adjusted models, each unit increase in gender norm attitudes score (reflecting more equitable gender norm attitudes) was associated with +0.09 LAZ (95% CI: 0.02, 0.16) and a decreased odds of stunting (adjusted odds ratio [AOR]: 0.86; 95% CI: 0.74, 1.01); each unit increase in social support score was associated with +0.11 LAZ (95% CI: 0.05, 0.17, p < 0.010) and decreased odds of stunting (AOR: 0.83; 95% CI: 0.73, 0.96). Each unit increase in decision‐making autonomy was associated with a 6% reduced odds of stunting (AOR: 0.94; 95% CI: 0.89, 0.996, p = 0.04). Interventions and social programming that strengthen these maternal capabilities may improve child nutritional status.